2013
DOI: 10.3109/00365521.2013.799222
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter randomized controlled trial comparing the performance of 22 gauge versus 25 gauge EUS–FNA needles in solid masses

Abstract: A significant difference was found between the two types of needles in terms of reduced visualization of the 25G needle and suboptimal performance rating. However, this did not impact on overall results since both needles were equally successful in terms of a high diagnostic yield and overall accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 20 publications
0
50
1
3
Order By: Relevance
“…A 25-gauge needle is therefore recommended to puncture the head of the pancreas 4 . Several studies have compared the performance characteristics of a 22-gauge needle with those of a 25-gauge FNA needle for sampling pancreatic masses, but most have failed to demonstrate superiority of either needle [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . A recent systematic review and meta-analysis of EUS-FNA for solid pancreatic masses, including a large cohort of patients, revealed that a 25-gauge needle was more sensitive than a 22-gauge needle 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A 25-gauge needle is therefore recommended to puncture the head of the pancreas 4 . Several studies have compared the performance characteristics of a 22-gauge needle with those of a 25-gauge FNA needle for sampling pancreatic masses, but most have failed to demonstrate superiority of either needle [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . A recent systematic review and meta-analysis of EUS-FNA for solid pancreatic masses, including a large cohort of patients, revealed that a 25-gauge needle was more sensitive than a 22-gauge needle 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although it may be considered that a larger-sized needle provides higher diagnostic yield, it is observed that the size of the needle does not affect the diagnostic yield in many studies. Vilmann et al (12) did not determine any difference in the diagnostic accuracy of 22 G vs. 25 G needles in the diagnosis of intra-abdominal solid masses. Likewise, in the study of Camellini et al (13), no significant difference was determined between the efficacy of 22 G and 25 G needles.…”
Section: Which Eus Needle Is More Effective?mentioning
confidence: 99%
“…Because the 19G aspiration needles are more rigid [56,57], they are not routinely recommended for head pancreatic biopsies [49]. However, the diagnostic accuracy for body/tail pancreatic lesions is better with 19G needles than with 22G needles [57,58], especially for the differential diagnosis of pancreatic masses.…”
Section: Endoscopic Ultrasound Fine-needle Aspirationmentioning
confidence: 99%